2022
DOI: 10.1186/s12885-022-10436-3
|View full text |Cite
|
Sign up to set email alerts
|

Predictive nomogram based on serum tumor markers and clinicopathological features for stratifying lymph node metastasis in breast cancer

Abstract: Background This study was aimed to establish the nomogram to predict patients’ axillary node status by using patients’ clinicopathological and tumor characteristic factors. Methods A total of 705 patients with breast cancer were enrolled in this study. All patients were randomly divided into a training group and a validation group. Univariate and multivariate ordered logistic regression were used to determine the predictive ability of each variable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“… 26 , 27 , 28 It participates in the inhibition of cell differentiation and apoptosis, 29 and plays an important role in tumour metastasis. 30 A significant association was found between elevated CEA levels and tumour size, lymph node metastasis, and advanced‐stage breast cancer. 31 , 32 , 33 Studies have found that CEA levels were affected by drugs such as trastuzumab and paclitaxel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 26 , 27 , 28 It participates in the inhibition of cell differentiation and apoptosis, 29 and plays an important role in tumour metastasis. 30 A significant association was found between elevated CEA levels and tumour size, lymph node metastasis, and advanced‐stage breast cancer. 31 , 32 , 33 Studies have found that CEA levels were affected by drugs such as trastuzumab and paclitaxel.…”
Section: Discussionmentioning
confidence: 99%
“…CEACAM5, also known as carcinoembryonic antigen (CEA), has been reported to be overexpressed in several cancers, especially colon cancer 26–28 . It participates in the inhibition of cell differentiation and apoptosis, 29 and plays an important role in tumour metastasis 30 . A significant association was found between elevated CEA levels and tumour size, lymph node metastasis, and advanced‐stage breast cancer 31–33 .…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between VI and positive lymph nodes in early breast cancer has also been explored. Geng et al [30] showed that VI was an independent prognostic factor for positive axillary lymph nodes in patients undergoing SNLB, including pathological T3 stage, clinical N0 stage, and some N1 stage patients. In addition, Liu et al [31] showed that VI was an independent predictor of non-SLN metastasis in T1-2 breast cancer patients with only one SLN metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…A non-invasive tool for predicting SLN status could be beneficial in preoperatively identifying patients at risk of postoperative complications associated with the requirement for PMRT following IBR. Although there are several nomograms for predicting axillary node status 1820 , most of them include variables that are not routinely available in a preoperative setting. Moreover, predictive tools to identify patients with cN0 breast cancer at high risk of macro-SLNM indicating the need for PMRT, are still lacking.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are several nomograms for predicting axillary node status [18][19][20] , most of them include variables that are not routinely available in a preoperative setting. Moreover, predictive tools to identify patients with cN0 breast cancer at high risk of macro-SLNM indicating the need for PMRT, are still lacking.…”
Section: Introductionmentioning
confidence: 99%